Relações Públicas e Marketing Digital: análise das estratégias utilizadas pela FOP Company e Reformando Camiseteria no Instagram - Pinto, Hanna Victória Assante (Brasil, 2021)
Due to the COVID-19 pandemic, the digital world has developed exponentially and has transformed the way the market works. Given the growth of virtual companies on Instagram since 2020, there was a need to study how Public Relations and Digital Marketing can be used in this context. Thus, this research aims to discuss the role of Public Relations and Digital Marketing in digital companies, analyzing the strategies used by FOP Company and Reformando Camiseteria on Instagram. In addition, the current work has the nature of exploratory basic research, with a qualitative approach and the procedure used bibliographical research and case study, as well as content analysis. Thus, it was possible to observe that companies, despite being present in the online environment, still do not efficiently use PR and Digital Marketing strategies. Therefore, this research allows micro-entrepreneurs to have in-depth knowledge about the strategies needed to act in the digital, showing in a clear and dynamic way the benefits of acting strategically.